PENGARUH DISIPLIN KERJA DAN PENGEMBANGAN KOMPETENSI TERHADAP KINERJA KARYAWAN PADA PT. DROPINDO KREASI FORTUNA - Mariatul Qibtiyyah; Tarwijo Tarwijo (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the effect of work discipline and competency development on employee performance, both partially and simultaneously, at PT Dropindo Kreasi Fortuna. This research employed a quantitative method with an associative approach. The data analysis techniques included validity test, reliability test, classical assumption test, multiple linear regression analysis, correlation coefficient test, coefficient of determination test, as well as t-test and F-test. The population of this study consisted of all employees of PT Dropindo Kreasi Fortuna. The sampling technique used was saturated sampling, resulting in a total sample of 53 respondents.The results of the coefficient of determination test indicated that work discipline and competency development contributed 57.8% to employee performance, while the remaining 42.2% was influenced by other variables not examined in this study. The multiple linear regression analysis produced the equation Y = 0.566 + 0.360X1 + 0.622X2, which indicates that even without the influence of work discipline (X1) and competency development (X2), employee performance still has a value of 0.566. Furthermore, the simultaneous test showed that the calculated F-value (34.303) was greater than the F-table value (3.18), leading to the rejection of H0 and acceptance of Ha. Therefore, it can be concluded that work discipline and competency development simultaneously have a significant effect on employee performance at PT Dropindo Kreasi Fortuna.